IMPLEMENTASI PEMBELAJARAN TEMATIK OLEH GURU KELAS PADA SEKOLAH DASAR DI-KECAMATAN LEMBAH SEGAR KOTA SAWAHLUNTO - Doni Warman (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
This study aims to determine the way of planning, how to implement, how the assessment of thematic learning by classroom teachers in elementary school in the district. Fresh Valley. City of Sawahlunto. Type of research that writer use is Etnografi research. Data collection techniques are done by triangulation, inductive data analysis and qualitative research results emphasize the meaning of the generalization. Informants in this study are primary informants and additional informants . Data collection techniques in research are observation, interview and documentation. The result of the implementation of thematic teaching by the classroom teacher at elementary school in sub-district of fresh valley of sawahlunto city is at learning planning stage. The class teacher at SD in Kecamatan Lembah Segar Kota Sawahlunto uses various ways but the same goal is by analyzing SKL, KD and Syllabus designing RPP using the thematic RPP model, and listing RPP themes and components. the implementation of Thematic learning by classroom teachers is done by classroom teachers using: tying some subjects with one theme, explaining the material with various learning methods, inviting students to be more active in learning, creating a more comfortable classroom atmosphere, delivering the material in a relaxed but assessment phase, all teachers use evaluation way for KI-1, KI-2, and KI-4 done day with assessment rubric. For the assessment of KI-3 the teacher performs the assessment by means of training per 1 lesson and for daily test is done on 1 sub theme. For the evaluation of spiritual and social attitudes using a range of SB, B, C or K values.